PHARMACOLOGICAL TREATMENTS OF COVID-19 – A REVIEW - CHERUMANALIL, JEEJA MATHUMMEL; THAYYIL, JAYAKRISHNAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Now the world stands in the fight against coronavirus disease 2019 (COVID-19), with its early origin from Wuhan city in China. It has evolved into a global pandemic resulting into a significant burden to the human race. As per WHO, on July 31, 2020, there were 170 million cases reported all over the world, with 6.73 lakhs deaths. There is no effective treatment so far discovered for the severe acute respiratory syndrome-CoV2. Many pharmacological agents/therapies are being used or considered for treatment. In many countries, physicians are giving COVID-19 patients treatment that has not been approved for this disease. They are treating patients using medications outside their indicated, approved uses and without study protocols, with little scientific evidence. At present, there is no evidence from randomized clinical trials (RCTs) that any potential therapy improves outcomes in patients with COVID-19. There are no clinical trial data supporting any prophylactic therapy. Along with Solidarity trial, many active clinical treatment trials are underway. This narrative review summarizes current evidence regarding major proposed treatments, repurposed or experimental, for COVID-19 and provides a summary of current clinical experience and treatment guidance for this pandemic novel coronavirus.